2021
DOI: 10.4103/ijo.ijo_1365_21
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of voriconazole and amphotericin B in corneal preservative media

Abstract: Purpose: To evaluate the efficacy of voriconazole and amphotericin B in McCarey–Kaufman (MK) media. Methods: MK media vials were supplemented with either voriconazole at 1, 2, 20, 50, 100 μg/mL or amphotericin B at 0.5, 1, 2, 10, 20 μg/mL. The standard inoculum of the American Type Culture Collection (ATCC) strain of Candida albicans , Aspergillus flavus , and Fusarium keratinoplasticum was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Kumar et al have developed nanostructured lipid carriers loaded with itraconazole and shown that this system can be an effective approach, with adequate activity against fungi and less local side effects [ 91 ]. While several in vitro and in vivo experimental studies have highlighted promising results using this treatment method, further controlled studies are necessary for its use on humans [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Treatment Approachesmentioning
confidence: 99%
“…Kumar et al have developed nanostructured lipid carriers loaded with itraconazole and shown that this system can be an effective approach, with adequate activity against fungi and less local side effects [ 91 ]. While several in vitro and in vivo experimental studies have highlighted promising results using this treatment method, further controlled studies are necessary for its use on humans [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Treatment Approachesmentioning
confidence: 99%
“…Efforts to prevent tissue contamination have led to improvement in disinfection protocols and reduced warming time during tissue processing [ 4 ]. Additionally, in vitro studies have demonstrated the effectiveness of antifungal supplementation in hypothermic storage [ 5 9 , 17 , 18 ], underscoring its potential in preventing fungal infections in EK procedures. Furthermore, recent studies suggest that antifungal supplementation could be cost-effective for EK surgeries [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…To provide a comprehensive overview of the current research, we have included a table [ Table 6 ] summarizing the key details from similar studies examining different antifungals. [ 16 21 22 ]…”
Section: Discussionmentioning
confidence: 99%